RANCANGAN PEMETAAN HASIL PRODUKSI PERTANIAN UNGGULAN DI KABUPATEN SERDANG BEDAGAI - Alfonsus Situmorang; Yolanda Y. P. Rumapea; Jimmy F. Naibaho; Indra Kelana Jaya; Albert Harianja (Universitas Methodist Indonesia, 2023)
The availability of agricultural land that is wide enough is a factor in the diversity of agricultural products. With the support of available technology, the community can determine the superior commodities from these agricultural products. In this study to determine the results of superior agricultural production, the Location Quotient method can be used. Method. In this study, data on area and agricultural production were used for 1 year (2020-2021) from the Serdang Bedagai Agriculture Service. The results of the research are in the form of a mapping system for superior agricultural production from 5 types of plants, namely rice, corn, cassava, watermelon, chili in Serdang Bedagai Regency. Mapping is designed using arcgis software to determine superior commodities. The test results with the Location Quotient method on cassava plant species with the highest value of production were 12.9, rice 4.7, chili 3.25, corn 1.53, watermelon 1.26.